Rekruitmen, Seleksi, Pelatihan Terhadap Kinerja Karyawan Pada Hotel Aria Gajayana - Yuyuk Liana (INSPIRASI : JURNAL ILMU-ILMU SOSIAL, 2022)
Recruitment is an effort to find workers to get as many prospective employees as possible so that companies have a greater opportunity to make choices for prospective workers who are considered to have qualification standards within the company. The data of this study were obtained by distributing questionnaires. The sample in this study were 100 respondents. The results of this study show that recruitment, selection, training have an effect on employee performance